2018
DOI: 10.1590/0100-29452018408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional and Alternative Products on Postharvest Disease Control in Avocados

Abstract: Postharvest diseases constitute a serious problem for avocado commercialization. Thus, the present study aimed to evaluate the effect of conventional and alternative products in controlling diseases affecting ‘Hass’ avocados in the field and in the postharvest by carrying out physicochemical characterization of fruits subjected to postharvest treatments. In the field, besides the management adopted by the farmer, seven products were sprayed three times during fruiting for evaluation. Postharvest products were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
16
0
4
Order By: Relevance
“…According to Fischer et al (2018), soluble solids of avocado treated with sodium bicarbonate have been slightly reduced compared to the untreated control and this finding is in conformity with the results of the present research. These also agree with Fischer et al (2018) who reported that flesh firmness and peel colour of sodium bicarbonate treated avocado did not show a significant difference when compared to the control.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to Fischer et al (2018), soluble solids of avocado treated with sodium bicarbonate have been slightly reduced compared to the untreated control and this finding is in conformity with the results of the present research. These also agree with Fischer et al (2018) who reported that flesh firmness and peel colour of sodium bicarbonate treated avocado did not show a significant difference when compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…The US FDA recommends that sodium bicarbonate could be applied on food substrates with no limitation other than Good Manufacturing Practice (GMP) specifications (eCFR, 2020 Fischer et al (2018) reported that avocado (cv. Hass) fruits treated with 2% w/v sodium bicarbonate have exhibited a significant reduction in postharvest disease of 'anthracnose'.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several research efforts aimed towards finding safer alternative technologies have been made in the past decade or so. These alternative methods can be classified into physical heat treatments (such as hot water dips, steaming, dry heat and forced air), irradiation, controlled atmospheres, electrolysed water, biological control, plant extracts (such as essential oils) and elicitors (e.g., chitosan and jasmonates) [17]. This review explores the different types of postharvest constraints of avocados and the non-chemical treatments available to alleviate their impacts.…”
Section: Constraints During Marketingmentioning
confidence: 99%
“…Most of the injuries can act as port of entries for postharvest pathogens after ripening during marketing. Therefore, severely damaged fruits can be easily isolated and culled before marketing [17]. Injuries, such as lenticel damage, instantly become apparent after any form of mishandling as they cause small dark spots about 1-5 mm diameter appear, which are more severe when fruit are harvested wet [19].…”
Section: Mechanical Damagementioning
confidence: 99%
“…Plant diseases are responsible for considerable losses in crops of economic importance. For the control of plant diseases, chemical, physical and biological methods have been used [1,2,3]. However, the indiscriminate use of chemical agents in agriculture causes serious risks to the environment and to the human health, creating a trend to the use of alternative methods of disease control.…”
Section: Introductionmentioning
confidence: 99%